Kebijakan dan Strategi Pemerintah Kabupaten Bandung Barat dalam Penanggulangan Kemiskinan - Huraerah, Abu; Kurniasih, Nina; Suyono, Sinta Yulianti (Jurnal Publisitas, 2026)
Purpose of the study to analyze the policies and strategies of the West Bandung Regency Government in poverty alleviation. The research method used is a qualitative method. Data collection techniques used are unstructured interviews, focus group discussions, observations, and document studies. The results of the study indicate that several policies of the West Bandung Regency Government in poverty alleviation are manifested in the form of the West Bandung Regency Regent Regulation on Regional Action Plan (RAD/Rencana Aksi Daerah) for Poverty Alleviation, the West Bandung Regency Regional Regulation on the Implementation of Legal Aid for the Poor, the Regional Poverty Alleviation Plan (RPKD/Rencana Penanggulangan Kemiskinan Daerah) for 2025-2030, and specific policies in the program of "Bandung Barat Ca'ang". The West Bandung Regency Government's strategy for poverty alleviation includes economic empowerment, social protection, optimizing regional autonomy through Village SDGs, and area-based data analysis. Poverty alleviation must be carried out through a multidimensional approach. The West Bandung Regency Government, as the party most responsible for poverty alleviation, is required to have a strong commitment to formulating and implementing poverty alleviation policies and strategies. The poverty alleviation paradigm, which views poverty solely as an economic issue, is one of the causes of the failure of poverty alleviation efforts. Poverty alleviation is not simply about providing assistance to meet the needs of the poor. Poverty is a multidimensional (especially economic, cultural, and structural) and multisectoral problem with diverse, urgent characteristics that require systematic, integrated, and comprehensive measures. Therefore, poverty alleviation measures are needed, supported by accurate data, targeted policy direction, and strategies. Furthermore, a Regional Regulation concerning the Handling of the Poor in West Bandung Regency is needed. This Regional Regulation serves as the legal basis for the implementation of various programs and activities to improve the welfare of the poor.